Should Social Security Benefits Be Means Tested? - Feldstein, Martin S. (Journal of Political Economy, 1987)
Social-security retirement benefits distort the saving decisions of workers who are rational enough to save for their future. Since the implicit rate of return in an unfunded social-security program is less than the marginal product of capital, the resulting decline in saving causes a welfare loss. The present paper examines the conditions under which the welfare loss can be reduced by replacing the current universal social-security program with a means-tested program that pays benefits only to those individuals with little or no other retirement income or assets. Copyright 1987 by University of Chicago Press.